Mechanisms of Chromium Removal from Water and Soil Using Bioleached Nano Zero-Valent Iron-Mediated Biochar via Co-Pyrolysis - Zhiyi Liu; Shuhong Zhou; Yubing Cai; Xuehai Zhang; Muhammad Shaaban; Qi-an Peng; Yajun Cai (Nanomaterials)
Biological charcoal loaded with nano zero-valent iron (nZVI@BC) was synthesized using the bioleaching co-pyrolysis method. This study analyzed the formulation sequence of nZVI@BC and its influence on chromium elimination from water and soil, along with the involved mechanisms. The bioleaching method facilitated ionic iron incorporation onto biochar in the form of yellow potassium ferroalum compounds, which were reduced to Fe0 by H2, CO, and CH4 generated during biomass co-pyrolysis. In aqueous conditions, the removal capacity of Cr(VI) by nZVI@BC increased by 72.01% and 66.92% compared to biochar (BC) and biochar–bioleachate composite (BBC), respectively. Under optimal conditions, nZVI@BC eliminated 90.11% of 20 mg/L Cr(VI), with experimental data fitting the Freundlich and pseudo-second-order kinetic models. The nZVI@BC also showed a passivation effect on chromium in soil; after 45 days, the exchangeable state of chromium was reduced by 12.89%, while the residual state increased by 10.45%. This enhancement in chromium elimination from soil was evident, as the residual state increased more for nZVI@BC (10.45%) than for BC alone (9.67% and 8.48%). Soil physicochemical properties and microbial community abundance improved as well. Cr(VI) removal mechanisms involved adsorption, reduction, and co-precipitation in water, while soil mechanisms included surface adsorption, electrostatic attraction, ion exchange, and complexation. The synthesis of nZVI@BC offers a novel method for creating iron-modified materials to effectively remove Cr(VI).